Analisis Pengelolaan Obat di Puskesmas Panite Amanuban Selatan Kabupaten Timor Tengah Selatan - Kristianti N. Kase; Masrida Sinaga; Galuh Wiedani K.D. Larasati (Jurnal Rumpun Ilmu Kesehatan, 2025)
Drug management is a series of activities in health development that includes planning, procurement, receipt, storage, and distribution of drugs. This study aims to analyze drug management at Panite Health Center. This research used a qualitative descriptive method with data collection through interviews, observation, and documentation in June–July 2025. The informants of this study were three people, consisting of one main informant (Head of Panite Health Center), one expert informant (Pharmacist), and one supporting informant (Pharmaceutical Technical Staff). The results showed that drug planning at Panite Health Center has been running well. Drug procurement is carried out monthly and quarterly through the Health Office drug warehouse, but often the quantity received does not match the request. Drug receipt is done by the health center picking it up directly or being delivered by the health office. Drug storage is still constrained by limited space, so some drugs are stored in their primary packaging. Drug distribution is managed by pharmaceutical technical staff and adjusted to the needs of each sub-units, but there are often drug shortages during distribution. Therefore, the Panite Health Center needs to pay more attention to the implementation of applicable pharmaceutical service standards to overcome problems in drug management.